Obporodna analgezija in izidi porodov v Sloveniji - Bergant, Jernej (Zdravniški vestnik, 2016)
Background: Effective labour analgesia is important for the mother and the newborn although it might have adverse effects on the labour outcome. Due to our limited data, the slovene obstetricians, when counselling prospective mothers, mainly rely on foreign data the findings of which are difficult to interpret because of differences in labour management between countries. The aim of this retrospective analysis is to evaluate the effects of labour analgesia on the obstetric outcome in slovene maternity units. Methods: A retrospective study using data from the National perinatal information system was done, and 168863 deliveries were analysed. All singletons (cefalic presentation and gestational age of 37 weeks 0/7 and more) from all 14 Slovenian maternity wards, born from 1st Jan 2003 to 31th Dec 2012 were included. Stillbirths, children with congenital abnormalities and elective caesarean sections were excluded. Univariate analysis and multivariate logistic regression were used to examine the impact of risk factors on birth outcomes. Results: Multivariate logistic regression showed that epidural and intravenous analgesia compared to the absence of analgesia present a higer risk factor for labour duration above 7 hours (OR 5.1; 95 % CI 4.8-5.4 for epidural analgesia), (OR 1.8; 95 % CI 1.8-1.9 for intravenous analgesia) and for vacuum extraction of the fetus (OR 4.0; 95 % CI 3.7-4.4 for epidural analgesia), (OR 1.7; 95 % CI 1.6-1.8 for intravenous analgesia). Only epidural analgesia increases the risk for occipitoposterior presentation (OR 1.8; 95 % CI 1.7-2.0). The risk for caesarean section decreases with intravenous (OR 0.4; 95 % CI 0.4-0.5) as well as with epidural analgesia (OR 0.6; 95 % CI 0.5-0.6). Neither intravenous nor epidural analgesia incure any risk factor for low Apgar score (< 6) (OR 1.0; 95 % CI 0.8-1.1 for intravenous analgesia) (OR 0.9; 95 % CI 0.7-1.2 for epidural analgesia) or pathological cardiotocogram (OR 1.0; 95 % CI 0.9-1.0 for intravenous analgesia) (OR 1.0; 95 % CI 0.9 - 1.1 for epidural analgesia). Conclusions: Intravenous and epidural analgesia affected the course and outcome of labour. Mothers under epidural anagesia had a higher risk of labour longer than 7 hours, incidence of occipitoposterior presentation and vaccum extraction of fetus. Pain control during labour reduced the risk of caesarean section and had no adverse effects on the neonate.
Keywords: caesarean section; carski rez; childbirth; epidural analgesia; epiduralna analgezija; intravenous analgesia; intravenska analgezija; porod